Symptomatology following loss and trauma: Latent class and network analyses of prolonged grief disorder, posttraumatic stress disorder, and depression in a treatment‐seeking trauma‐exposed sample. Issue 1 (6th February 2019) - Djelantik, A. A. A. Manik J.; Robinaugh, Donald J.; Kleber, Rolf J.; Smid, Geert E.; Boelen, Paul A.
Abstract : Background: Although bereavement is likely a common stressor among patients referred to a psychotrauma clinic, no study has yet examined the co‐occurrence and relationships between symptoms of prolonged grief disorder (PGD), posttraumatic stress disorder (PTSD), and major depressive disorder symptoms in this population. Method: In a sample of patients seeking treatment following psychological trauma ( n  = 458), we used latent class analysis to identify classes of patients sharing the same profile of PGD, PTSD, and depression symptoms. We then used network analysis to investigate the relationships among these symptoms and with loss‐related variables. Results: Most participants (65%) were members of a class that exhibited elevated endorsement of PGD symptoms. PGD, PTSD, and depression symptoms hung together as highly overlapping but distinguishable communities of symptoms. Symptoms related to social isolation and diminished sense of self bridged these communities. Violent loss was associated with more difficulty accepting the loss. The loss of close kin was most strongly associated with difficulty moving on in life. Conclusions: PGD symptoms are common in trauma‐exposed bereaved adults and closely associated with symptoms of PTSD and depression, illustrating the importance of assessing bereavement and PGD symptoms in those seeking treatment following trauma.